Commitment and Behavior Change: A Meta-Analysis and Critical Review of Commitment-Making Strategies in Environmental Research. (January 2013) - Lokhorst, Anne Marike; Werner, Carol; Staats, Henk; van Dijk, Eric; Gale, Jeff L.
Commitment making is commonly regarded as an effective way to promote proenvironmental behaviors. The general idea is that when people commit to a certain behavior, they adhere to their commitment, and this produces long-term behavior change. Although this idea seems promising, the results are mixed. In the current article, the authors investigate whether and why commitment is effective. To do so, the authors first present a meta-analysis of environmental studies containing a commitment manipulation. Then, the authors investigate the psychological constructs that possibly underlie the commitment effect. They conclude that commitment making indeed leads to behavior change in the short- and long term, especially when compared with control conditions. However, a better understanding is needed of the possible underlying mechanisms that guide the commitment effect. The authors see commitment making as a potentially useful technique that could be improved by following up on findings from fundamental research. They provide suggestions for future research and recommendations for improving the effectiveness of commitment-making techniques.